Personas Identification for the Users of the Information System - Zergaw, Tihitina Hailu (Univerzita Pardubice, 2024)
This thesis delves into persona identification by focusing on foreign student users of information systems at the University of Pardubice. The primary objective is to identify the most suitable method for defining the main target group of users, with a particular emphasis on understanding the expectations and challenges faced by this specific user group. The research journey involved exploring three different approaches to persona development: qualitative, quantitative, and mixed approach. Given the convenience of data collection and analysis, the qualitative approach was adopted, utilizing surveys as the chosen method to develop the persona. Whereby the analysis used mixed methodology since there is a bit of a statistical part and a qualitative part. To ensure the relevance and effectiveness of the survey questionnaire, criteria for a good information system were established. Three main criteria, each with three sub-criteria, were used to measure the goodness of the system. The questionnaire was distributed to eighteen foreign students and three Czech students, the latter serving as a comparative group. The research questions guided the exploration into key expectations, requirements, challenges, and the design of an effective persona identification system tailored for foreign student users at Pardubice University. The study revealed that foreign student users faced challenges related to language barriers, a lack of assistance in navigating the system, difficulties in course registration, and a perception of the system as complex and unclear. The qualitative approach, although valuable, presented limitations due to issues of confidentiality, resulting in a manual data collection process with a small number of participants and manual data analysis. In conclusion, this research underscores the importance of selecting an appropriate method for persona creation in the context of information systems. The developed persona provides valuable insights into the unique needs and challenges faced by foreign student users at Pardubice University, offering a foundation for future enhancements to the information system's user experience.
Keywords: persona; persona identification; user persona; user profiling; information system